Nurse Compliance of Electronic Nursing Care Documentation in Inpatient Rooms - Erny Prasetyowati; Puguh Widiyanto; Sri Hananto Ponco Nugroho (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Electronic Nursing Care contains various record files, such as medical records of doctors, nurses, and other health workers who collaborate to provide health services. Documentation of nursing care can be hampered due to several factors, such as nurse's knowledge, attitude, motivation, and compliance. This study aims to determine the relationship between factors of nurse compliance in documenting nursing care using Electronic Medical Records. This study used a cross-sectional approach with 41 subjects selected using total sampling. The data obtained was tested using the Spearman Rank test using IBM Statistics 25 for Windows. The measuring tool used was a questionnaire of knowledge, attitudes, motivation, and observations regarding compliance with filling out nursing care. The result obtained produced a p of 0.000 (p <0.05). There was a significant relationship between the knowledge, attitudes, and motivation of nurses with compliance in documenting nursing care using electronic medical records with the strength of a strong relationship with a positive pattern, meaning that the better the level of knowledge, attitudes, and motivation of nurses, the more obedient they will be toward documentation of nursing care with electronic medical records.